(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article provides an overview of theoretical studies on monolingualism, bilingualism, and trilingualism, examining their cognitive, linguistic, and sociocultural aspects. The research methodologies employed in these studies are explored, and the contributions of key researchers and their influential works in the field are discussed.